Dispersing Agents Impact Performance of Protonated Phosphonic Acid High-Temperature Polymer Electrolyte Membrane Fuel Cells - Jung, Jiyoon; Lim, Katie H.; Maurya, Sandip; Manriquez, Luis Delfin; Atanasov, Vladimir; Ahn, Cheol-Hee; Hwang, Seung Sang; Lee, Albert S.; Kim, Yu Seung (American Chemical Society, 2022)
The microstructure of ionomers plays a significantrole in the performance of high-temperature polymer electrolytemembrane fuel cells (HT-PEMFCs). Here, we establish directcorrelations between the properties of dispersing agents and themicrostructure of a protonated phosphonic acid ionomer. Mostimportantly, the formation of the porous structure of a protonatedphosphonic acid ionomer depends on the pKaof the liquid media.Namely, the acid-base interaction between the charged polymerand dispersing agents determines the porosity in the ionomer thinfilms. The HT-PEMFC performance increases with the level ofporosity of the ionomer, as the pores enable fast reactant gasaccessibility. This study concludes the importance of the pKaofionomers'dispersing media for the HT-PEMFC performance.